2014
DOI: 10.1111/bjet.12234
|View full text |Cite
|
Sign up to set email alerts
|

A social network analysis of teaching and research collaboration in a teachers' virtual learning community

Abstract: Analysing the structure of a social network can help us understand the key factors influencing interaction and collaboration in a virtual learning community (VLC). Here, we describe the mechanisms used in social network analysis (SNA) to analyse the social network structure of a VLC for teachers and discuss the relationship between face‐to‐face and online collaborations. In contrast to previous research applying SNA to analyse measuring indexes alone, we emphasise the mechanisms combining SNA, questionnaires, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 28 publications
2
25
0
2
Order By: Relevance
“…More learner‐centred learning activities could be conducted to underscore the importance of improved learner‐centred authority as assisted by mobile technology. Substantial work should focus on the surface‐supportive profile, which includes applying deep‐motive strategies to engage in m‐learning activities and the use of social network services to facilitate collaboration (Lin, Hu, Hu, & Liu, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More learner‐centred learning activities could be conducted to underscore the importance of improved learner‐centred authority as assisted by mobile technology. Substantial work should focus on the surface‐supportive profile, which includes applying deep‐motive strategies to engage in m‐learning activities and the use of social network services to facilitate collaboration (Lin, Hu, Hu, & Liu, ).…”
Section: Discussionmentioning
confidence: 99%
“…More learner-centred learning activities could be conducted to underscore the importance of improved learner-centred authority as assisted by mobile technology. Substantial work should focus on the surface-supportive profile, which includes applying deep-motive strategies to engage in m-learning activities and the use of social network services to facilitate collaboration (Lin, Hu, Hu, & Liu, 2016 and WhatsApp rather than sharing ideas with their peers. However, for the mixed profile, a multidirectional communication as occur through among social network applications can facilitate collective efforts to produce creative works.…”
Section: Roles On Approaches To M-learning Among Different M-learnimentioning
confidence: 99%
“…This result might be better explained from the perspectives of both social support and self-regulated learning. On the one hand, Lin, Hu, Hu, and Liu (2016) demonstrated the benefits of web-based learning because learners could seek online support, while tutors could provide guidance online (via communicative platforms such as emails, instant messaging applications, blogs). On the other hand, Za et al (2014) demonstrated that employees who are inclined to learn through the processes of reflecting, sharing, receiving support and making adjustments (i.e., self-regulation) could effectively offer different contexts to foster transfer of their knowledge gained from oversimplified cases to conceptually complex situations.…”
Section: Discussionmentioning
confidence: 99%
“…The individual influence scope and socialized relationships among individuals in the network can be described by "cohesion" [5]. The importance of one individual to other individuals in the network is described by "centrality" [6]- [8]. The individuals in the social network consist of core members and peripheral members [9].…”
Section: Background Literaturementioning
confidence: 99%
“…Hence the core members are more efficient for spreading information. Scholars constructed a three-dimensional analytical model to study the structural characteristics of cooperative networks [6]. Scholars also used SNA method to analyze the individuals' interactive behaviours and discuss the causes of some phenomenon [10].…”
Section: Background Literaturementioning
confidence: 99%